Implementasi Metode AHP Dalam Sistem Penunjang Keputusan Penerima KIP Kuliah - Putu Andhika Kurniawijaya; I Wayan Widi Karsana (JUKI : Jurnal Komputer dan Informatika, 2023)
Dhyana Pura University (Undhira) is one of the universities that accepts KIP students. Based on an interview with the Head of Student Affairs Undhira, the requirements to be accepted as a student with KIP pathway must meet several requirements. With data collection that is still manual, of course, it makes the selection process of KIP recipients who should be more appropriate to receive KIP do not receive cards due to errors in analyzing data. Based on these problems, the researcher proposes a Decision Support System in determining the recipients of the Smart Indonesia Card in order to facilitate the student affairs department to provide decision support in determining the receipt of KIP Lectures. The AHP method was chosen in the research of the KIP Lecture decision support system. The AHP method process is carried out by knowing the best alternative from many elements of choice using pair wise comparison with the involvement of several objectives and criteria. Decision making becomes complex because of the involvement of several objectives and criteria. The college KIP decision support system will be built web-based.